Regulatory Mechanisms of the NLRP3 Inflammasome, a Novel Immune-Inflammatory Marker in Cardiovascular Diseases - An, Na; Gao, Yonghong; Si, Zeyu; Zhang, Hanlai; Wang, Liqin; Tian, Chao; Yuan, Mengchen; Yang, Xinyu; Li, Xinye; Shang, Hongcai; Xiong, Xingjiang; Xing, Yanwei (Frontiers in Immunology, 2019)
The nod-like receptor family pyrin domain containing 3 (NLRP3) is currently the most widely studied inflammasome and has become a hot topic of recent research. As a macromolecular complex, the NLRP3 inflammasome is activated to produce downstream factors, including caspase-1, IL-1β, and IL-18, which then promote local inflammatory responses and induce pyroptosis, leading to unfavorable effects. A growing number of studies have examined the relationship between the NLRP3 inflammasome and cardiovascular diseases (CVDs). However, some studies have shown that the NLRP3 inflammasome is not involved in the occurrence of certain diseases. Therefore, identifying the mechanism of action of the NLRP3 inflammasome and its potential involvement in the pathological process of disease progression is of utmost importance. This review discusses the mechanisms of NLRP3 inflammasome activation and the relationship between the inflammasome and CVDs, including coronary atherosclerosis, myocardial ischemia/reperfusion, cardiomyopathies, and arrhythmia, as well as CVD-related treatments.